Cuidados de enfermería en un recién nacido, basado en las taxonomías NANDA, NOC y NIC. - Santillán Guilcapi, Erika Karina (2016)
Nursing staff is trained to give direct attention to the patients both inside hospital and outside hospital, in response to their needs. This case study aims at apply nursing care in a newborn preterm moderate with appropriate weight for gestational age female with transient tachypnea of the newborn, surpassed hypothermia and hyperbilirubinemia, based on the NANDA (North American Nursing Diagnosis Association), NOC (Nursing Outcomes Classification), NIC (Nursing Interventions Classification); it is justified in the fourth Millennium Development Goal "Reducing infant death", for which the World Health Organization promotes strategies such as "Proper home care and treatment of complications in newborns" which is also supported by the objective 3 of the National Plan for Good living is "Improving the quality of life of the population." In the theoretical framework history, theory and model of Nursing, Nursing Care Process and description of the pathology addressed; for inpatient format valuation was used by functional health patterns of Marjory Gordon prepared by the career of Nursing at the National University of Chimborazo of the subject of PAE in Child Health, to identify problems of moderate newborn preterm and so formulate nursing diagnoses prioritizing their needs which are: ineffective breathing pattern, pattern ineffective infant feeding, neonatal jaundice, hypothermia and anxiety of the mother, the care plan was developed to implement them and thus contribute to improving the health, 4-hospital visits took place. For non-hospital model parent-child interaction Kathryn Barnard was used to improve maternal Operation 10 home visits were made through the implementation of educational plans aimed at the mother. The assessment was consistent throughout the DIANA score to obtain the expected results. Stability and adaptation of the newborn to their environment was achieved.